Differential tissue response to growth hormone in mice. Issue 7 (23rd May 2018) - Berry, Ryan; McGinnis, Graham R.; Banerjee, Ronadip R.; Young, Martin E.; Frank, Stuart J.
Abstract : Growth hormone (GH) has been shown to act directly on multiple tissues throughout the body. Historically, it was believed that GH acted directly in the liver and only indirectly in other tissues via insulin‐like growth hormone 1 (IGF‐1). Despite extensive work to describe GH action in individual tissues, a comparative analysis of acute GH signaling in key metabolic tissues has not been performed. Herein, we address this knowledge gap. Acute tissue response to human recombinant GH was assessed in mice by measuring signaling via phospho‐STAT5 immunoblotting. STAT5 activation is an easily and reliably detected early marker of GH receptor engagement. We found differential tissue sensitivities; liver and kidney were equally GH‐sensitive and more sensitive than white adipose tissue, heart, and muscle (gastrocnemius). Gastrocnemius had the greatest maximal response compared to heart, liver, white adipose tissue, and whole kidney. Differences in maximum responsiveness were positively correlated with tissue STAT5 abundance, while differences in sensitivity were not explained by differences in GH receptor levels. Thus, GH sensitivity and responsiveness of distinct metabolic tissues differ and may impact physiology and disease. Abstract : Historically, growth hormone was believed to only act directly on the liver. It has since been shown to have direct effects on most tissue types throughout the body. Here, we describe the differential growth hormone sensitivity and maximal responsiveness of five major tissue types in mice.